Do Correlations Between Mindfulness Components and Rumination in Student Athletes Support Mindfulness Training to Reduce Rumination?. Issue 4 (August 2021) - Tingaz, Emre Ozan; Çakmak, Soner
In the present study, we examined the relationship between mindfulness and rumination among student-athletes. Ninety-seven young adult student-athletes (38.1% female, 61.9% male; M age  = 22.52, SD  = 3.53) completed both the Mindfulness Inventory for Sport and the Ruminative Thought Style Questionnaire. Among these participants, we observed a significant positive correlation between rumination and the awareness sub-dimension of mindfulness. We also observed significant negative correlations between rumination and two scores from the Mindfulness Inventory for Sport: non-judgment and overall mindfulness . Awareness, non-judgment, and mindfulness were all significant predictors of rumination in a linear regression analysis. While these are correlational data that do not permit causal inferences, these findings raise the possibility, in this population, that awareness triggers ruminative thoughts and overall mindfulness might represent a coping tool for rumination. Further research is needed to test this possibility.